Inkjet-printed all solid-state electrochromic devices based on NiO/WO3 nanoparticle complementary electrodes. Issue 1 (27th November 2015) - Cai, Guofa; Darmawan, Peter; Cui, Mengqi; Chen, Jingwei; Wang, Xu; Eh, Alice Lee-Sie; Magdassi, Shlomo; Lee, Pooi See
Abstract : An all solid-state complementary electrochromic device with large optical modulation was assembled by inkjet-printed NiO and WO3 electrodes. Abstract : Nanostructured thin films are important in the fields of energy conversion and storage. In particular, multi-layered nanostructured films play an important role as a part of the energy system for energy saving applications in buildings. Inkjet printing is a low-cost and attractive technology for patterning and deposition of multi-layered nanostructured materials on various substrates. However, it requires the development of a suitable ink formulation with optimum viscosity, surface tension and evaporation rate for various materials. In this study, a versatile ink formulation was successfully developed to prepare NiO and WO3 nanostructured films with strong adhesion to ITO coated glass using inkjet printing for energy saving electrochromic applications. We achieved a high performance electrochromic electrode, producing porous and continuous electrochromic films without aggregation. The NiO film with 9 printed layers exhibits an optical modulation of 64.2% at 550 nm and a coloration efficiency (CE) of 136.7 cm 2 C −1 . An inkjet-printed complementary all solid-state device was assembled, delivering a larger optical modulation of 75.4% at 633 nm and a higher CE of 131.9 cm 2 C −1 among all solid-state devices. The enhanced contrast is due to the printed NiO film that not only performs as an ion storage layer, but also as a complementary electrochromic layer.